(untitled) (The Review of Diabetic Studies, 2025)
Background: Healthcare systems increasingly face complex patient needs that require coordinated contributions from multiple medical specialties. Fragmented care across departments has been associated with delayed decision-making, inefficiencies, and suboptimal patient outcomes, highlighting the growing importance of integrated healthcare systems. Objective: This systematic review aims to examine how multispecialty medical integration influences patient pathways and optimizes clinical, organizational, and patient-centered outcomes across healthcare settings. Methods: A systematic review was conducted in accordance with PRISMA guidelines. Peer-reviewed studies published between 2016 and 2025 were retrieved from PubMed, Scopus, and Web of Science. Eligible studies focused on integrated or multidisciplinary healthcare models involving two or more medical departments and reported outcomes related to patient pathways, quality of care, or system performance. Methodological quality was assessed using standardized appraisal tools. Results: The reviewed evidence indicates that integrated healthcare systems are associated with improved care coordination, reduced length of hospital stay, enhanced diagnostic accuracy, and lower readmission rates. Studies also reported improvements in patient satisfaction, continuity of care, and workforce collaboration, alongside organizational benefits such as improved efficiency and resource utilization. Conclusion: The findings demonstrate that multispecialty integration is a critical driver of optimized patient pathways and improved outcomes. Strengthening organizational structures, workforce collaboration, and digital enablers is essential for sustaining effective integrated healthcare systems.